Human Ecosystem Approach to The Dynamics of Sustainable Development in Komodo National Park, Indonesia - Imelda Masni Juniaty Sianipar; Aarce Tehupeiory; Arthuur Jeverson Maya; Huynh Le Anh Huy; Huynh Quoc Tuan; I Wayan Koko Suryawan (Universitas Muhammadiyah Tangerang, 2022)
This article aims to present the dynamics of sustainable development in Komodo National Park (KNP) using a human ecosystem model. The Human Ecosystem model is a coherent system of biophysical and social factors capable of adaptation and sustainability over time. A rural village in Komodo island, Labuan Bajo, East Nusa Tenggara, Indonesia can be considered a human ecosystem because it has identifiable boundaries, essential ecosystem functions, resource flows, social structures, social processes (including adaptive responses to changed conditions), and dynamic continuity over a period. In 2020, the “Jurassic Park” tourism project in Komodo National Park has become a hot topic on social media after a photo of a Komodo dragon blocking a truck popped up. The project’s rejection became the most popular topic on Twitter with the hashtag #savekomodo. Various groups believe that the project will destroy the Komodo dragon’s natural habitat, evict the local population, and be carried out solely for financial gain. As a result, it is critical to understand the current situation there. The HEM helps us identify the critical resources and the social systems, as well as the key flows that contribute to the dynamic of the human ecosystem in KNP. This article yields three important findings that should be considered in the future management of KNP. First and foremost, the Komodo dragon population is still stable, but it has the potential to decline in the long term due to changes in spatial planning, an increase in tourists, a decrease in food, and poaching. Second, expanding large-capital corporations that can replace local businesses such as boat rentals, car rentals, homestay businesses, restaurants, souvenirs, and tour guides/rangers will reduce local people’s income from tourism. Third, kinship relationships between Komodo dragons and the clan of Ota Moda are eroding because of fewer encounters between Komodo dragons and the island’s indigenous tribal communities. Artikel ini bertujuan untuk menyajikan dinamika pembangunan berkelanjutan di Taman Nasional Komodo (TNK) dengan menggunakan model human ekosistem. Model human ekosistem adalah system koheren dari faktor biofisik dan sosial yang mampu beradaptasi dan berkelanjutan dari waktu ke waktu. Sebuah desa di pulau Komodo, Labuan Bajo, Nusa Tenggara Timur, Indonesia dapat dianggap sebagai human ekosistem karena memiliki batas-batas yang dapat diidentifikasi, fungsi ekosistem esensial, aliran sumber daya, struktur sosial, proses sosial (termasuk respons adaptif terhadap kondisi yang berubah), dan kontinuitas dinamis selama suatu periode. Pada tahun 2020, proyek wisata “Jurassic Park” di Taman Nasional Komodo menjadi topik hangat di media sosial setelah muncul foto Komodo yang menghalangi truk. Penolakan proyek tersebut menjadi topik paling populer di Twitter dengan tagar #savekomodo. Berbagai kalangan percaya bahwa proyek tersebut akan menghancurkan habitat alami komodo, menggusur penduduk setempat, dan dilakukan semata-mata untuk keuntungan finansial. Akibatnya, sangat penting untuk memahami situasi saat ini di sana. HEM membantu untuk mengidentifikasi sumber daya penting dan sistem sosial, serta arus utama yang berkontribusi pada dinamika human ekosistem di TNK. Artikel ini menghasilkan tiga temuan penting yang harus dipertimbangkan dalam pengelolaan TNK di masa mendatang. Pertama dan terpenting, populasi komodo masih stabil, tetapi berpotensi menurun dalam jangka panjang karena perubahan tata ruang, peningkatan wisatawan, penurunan makanan, dan perburuan liar. Kedua, ekspansi perusahaan modal besar yang dapat menggantikan usaha lokal seperti persewaan kapal, persewaan mobil, usaha homestay, restoran, cinderamata, dan pemandu wisata/ranger akan mengurangi pendapatan masyarakat lokal dari pariwisata. Ketiga, hubungan kekerabatan antara komodo dan klan Ota Moda terkikis karena lebih sedikit pertemuan antara komodo dan komunitas suku asli pulau itu.